3D Ln-MOFs containing pentanuclear clusters exhibiting magnetic refrigeration and slow magnetic relaxation. Issue 26 (21st June 2017) - Liu, Feng; Huang, Hong; Gao, Wei; Zhang, Xiu-Mei; Liu, Jie-Ping
Abstract : Two isostructural 3D Ln-MOFs have been prepared under solvothermal conditions. The Gd-based MOF shows significant changes in magnetic entropy, while the Dy-based-MOF exhibits slow magnetic relaxation. Abstract : Two isostructural lanthanide-based 3D metal–organic frameworks (Ln-MOFs), [Ln5 (μ3 -OH)6 (TZI)3 (DMA)1.5 (H2 O)9.5 ]·DMA [Ln = Gd (1 ) and Dy (2 ), H3 TZI = 5-(1 H -tetrazol-5-yl)isophthalic acid], have been synthesized and structurally and magnetically characterized. In1 and2, the pentanuclear clusters with mixed (μ3 -OH)(μ2 -carboxylate) bridges are connected into 1D chains by μ2 -H2 O bridges, and then these chains are linked into 3D structures by the TZI ligands. The magnetic study suggests that1 shows significant cryogenic magnetocaloric effects (−Δ S m = 41.3 J kg −1 K −1, Δ H = 70 kOe, 2.5 K), whereas2 exhibits slow relaxation of magnetization.